Analogy and the development of catholic theology in Hans Urs von Balthasar (Doctor Virtualis, 2023)
The following essay is a tentative interpretation of Hans Urs von Balthasar’s Fathers, Scholastics and Ourselves. It proposes that analogy can be used to understand the similarities and differences between theological styles in different epochs. The analogy can be a heuristic tool to recognize the structural form that remains consistent throughout the ages, despite the unique expressions of this form according to the concrete and historical situation of the people being addressed by the message of the Gospel. This essay draws a comparison between the way Catholic theology and doctrine develop. In both cases, we find a paradigm of substantial homogeneity within a propositional or stylistic difference. The difference does not rule out a unity in a higher order. Different styles in theology are analogically united in an overarching and unchanging form of the truth revealed in Christ.
Keywords: Development of Doctrine; Catholic Theology; Analogy; Balthasar